School Energy Management in Efforts to Improve the Quality of Facilities and Infrastructure in Schools - Kurnia, Yudhi; Hidayati, Dian; Sukirman, Sukirman; Zuhaery, Mohammad (Universitas Ahmad Dahlan, 2024)
School energy management is one of the efforts to support the Sustainable Development Goals (SDGs), which focus on using clean and affordable energy and tackling climate change. This study aims to analyze and describe the planning, implementation, evaluation, and school energy management actions to improve the quality of facilities and infrastructure at Cendekia Muda Middle School and Muhammadiyah 8 Middle School Bandung. This study uses a qualitative method with a case study approach. Data was collected through observation, interviews, and documentation—data reduction techniques, data presentation, and concluding analyzed data. The study results show that planning for school energy management in both schools involves various parties, referring to government policies and considering technical, economic, social, and environmental aspects. The implementation of school energy management in both schools includes saving electricity, using renewable energy, managing waste, and counseling students and the community. Evaluation of school energy management in both schools was carried out using quantitative and qualitative indicators and involving internal and external parties. School energy management measures in both schools took the form of improving facilities, adding alternative energy sources, developing environmental programs, and collaborating with other parties. The results of this study are that school energy management in both schools has been carried out well and has positively impacted the quality of facilities and infrastructure, saving operational costs, increasing environmental awareness, and contributing to SDG achievement. This research implies that school energy management needs to be improved by continuously innovating, monitoring, evaluating, and socializing.